The Use of Finger Painting to Improve Fine Motor Skills of 5-6 Year Old Children at RA Al-Islamiyah Bebidas - Husniah; Darajah, Ulyah (Jurnal Profesi Guru Indonesia, 2025)
Fine motor activities can be done with various finger activities. The lack of enthusiasm and enthusiasm of children in developing fine motor skills makes researchers make improvements in the implementation of learning. This study aims to improve the fine motor skills of children in the 5-6 year old age group at RA AL-Islamiyah Bebidas through Finger painting activities. The research method in this study is classroom action research. In Finger painting activities, their fingers are trained to make various creations of their hands. This activity is carried out for two cycles. Namely, the first cycle is carried out for 5 days and the second cycle is carried out for 5 days. Based on the two cycles, it was found that through finger painting activities, students became more focused and motivated in learning. The results of the first cycle were 5 or 20% of people who could do it perfectly, 7 people or 28% and there were still many who could not, namely 52%. Then in the second cycle, 23 out of 25 children had succeeded in doing finger painting activities well. So it can be stated that finger painting activities can improve the fine motor skills of children in group B at RA Al-Islamiyah Bebidas.